2021
DOI: 10.1177/00027642211050901
|View full text |Cite
|
Sign up to set email alerts
|

Emotions During the COVID-19 Crisis: A Health Versus Economy Analysis of Public Responses

Abstract: People all over the world were under severe stress and were concerned about their health after a devastating pandemic struck the world in the form of a novel coronavirus disease (COVID-19) in late December 2019. Many nations imposed strict lockdowns and quarantines, causing citizens to maintain social isolation, throwing many companies to a halt. Thousands of people took to Twitter during these challenging circumstances to express their feelings about being caught in the middle of a storm. Twitter witnessed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…We have further provided details on the distribution of these specific emotions in all 3 subgroups in Table 3 . The results of this classification were largely consistent with the findings of recent studies that have profiled public emotions on social media during the COVID-19 pandemic [ 10 , 40 ], where the authors also found a prevalence of negative emotions such as fear.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We have further provided details on the distribution of these specific emotions in all 3 subgroups in Table 3 . The results of this classification were largely consistent with the findings of recent studies that have profiled public emotions on social media during the COVID-19 pandemic [ 10 , 40 ], where the authors also found a prevalence of negative emotions such as fear.…”
Section: Resultssupporting
confidence: 89%
“…On the one hand, the heightened situational uncertainty induced by the pandemic [39] could potentially lead to even stronger "negativity bias." Recent studies found a heightened prevalence of negative emotions or a negative emotional climate on social media during the early months of the pandemic [10,40]. On the other hand, findings from early COVID-19 scientific research were arguably important information sources of pandemic news.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of past research, the current authors created a novel measure of psychological wellbeing during the COVID-19 pandemic to address the current study’s research questions. The novel measure of psychological wellbeing contains 13 areas: (a) lifestyle and daily routines [ 16 ]; (b) general stress level [ 9 ]; (c) general sleep health beyond sleep quality [ 17 ]; (d) emotional health [ 18 ]; (e) physical health [ 19 ]; (f) sexual health [ 20 ]; (g) access to resources [ 21 ] such as food [ 22 ], toilet paper [ 23 ], cleaning supplies [ 24 ], heat [ 25 ], and electricity [ 26 ]; (h) job security [ 27 ]; (i) financial security [ 28 ]; (j) housing stability [ 29 ]; (k) sense of safety [ 30 ]; (l) sense of privacy [ 31 ]; and (m) sense of belonging to a social community [ 32 ]. These factors were selected because prior research has demonstrated their importance in contributing to psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…(T2A23) Trust in government was found to be a theme in other studies, particularly when it came to covid vaccine acceptance [62]. However, there were negative responses in the literature that captured overall disappointment on national responses to the pandemic that echos the sentiment captured here [65].…”
Section: Plos Onementioning
confidence: 86%